A Rare Case of Pneumonia Caused by Shewanella putrefaciens - Rajshree Patel; Albin Abraham; Johnson Thomas; Wanqing Zhi; Shadab Ahmed; Janice Verley (Case Reports in Medicine)
Shewanella putrefaciens is a gram-negative, nonfermentative, oxidase positive, motile bacillus that produces hydrogen sulphide. It is found widely in the nature especially in marine environments. In some very rare cases Shewanella putrefaciens can be a human pathogen. It can produce a wide variety of clinical syndromes including bacteremia as well as skin and soft tissue infections. However, pneumonia due to S. putrefaciens is rare; there are a total of 4 reported cases in the literature. We present a case of 63-year-old male who was presented to emergency room status after cardiac arrest, fell into sea water face down. On the second day of hospitalization, he was diagnosed to have pneumonia based on the clinical, radiological, and laboratory findings. Empirical antibiotic treatment with vancomycin and piperacillin/tazobactam combination was initiated. Gram-stained smear of endotracheal aspirate yielded gram-negative bacteria, and the isolate grown from endotracheal aspirate culture was identified as S. putrefaciens by Biomerieux API 20 NE technique. On review of the literature and according to culture and sensitivity results, therapy in our patient was changed to cefepime. Patient’s pneumonia improved with treatment with cefepime. We believe that our patient developed pneumonia evidently caused by S. putrefaciens, after near drowning in sea water. The pneumonia resolved after treatment with cefepime.